Specification for cast iron boilers for central heating and indirect hot water supply ( rated output 44 kW and above ) (BSI, 1989)
Cast-iron, Boilers, Hot-water boilers, Heating equipment, Indirect hot-water supply, Hot-water supply systems, Hot-water central heating, Central heating, Design, Pressure, Temperature, Ratings, Safety valves, Installation, Electric wiring systems, Automatic control systems, Inspection, Marking